Barriers to internationalisation of small and medium-sized enterprises (SMEs) in the Thai online fashion industry through social media - Turmratanasuwan, Tanawat (2018)
The objective of this study is to ascertain issues of specific barriers, owners’ perspectives, and determination in respect of the internationalisation of online SMEs through social media in the Thai fashion industry. This paper presents the findings of a study on the perceptions of barriers to internationalisation among 252 Thai online fashion SMEs which are operating through social media channels (e.g., Instagram or Facebook). Signiﬁcant differences in the perceptions of the barriers are identiﬁed according to the level of barriers to internationalisation under companies’ status: exporters, likely exporters, and non-exporters who are interested, and non-exporters who are not interested, including a comparison of internal and external barriers. Firm size, companies’ and owners’ age, and gender are also considered in order to establish whether or not they impact upon decisions related to international expansion; also taken into account are the preferred entry mode choices for new expansion into foreign markets. It has been concluded that firm size, number of Instagram followers, number of employees, and net income can influence decisions regarding the internationalisation of Thai online fashion SMEs, as can the operational periods of organisations. However, owners’ age and gender cannot impact the level of barriers to internationalisation, although older owners have more experience than do younger ones. Furthermore, marketing-based and firm-specific barriers are considered the biggest major barriers to internationalisation; indeed, these consist of the top minor barriers of high transportation and insurance costs, costs of operating overseas, a lack of experience in selling abroad, and not being known in foreign markets. Lastly, a quantitative methodology is adopted for this dissertation, which involves the use of linear regressions, a t-test, and one-way ANOVA as the main tools of investigation within the analysis.